2007
DOI: 10.1016/j.bbmt.2007.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Short Arm of Chromosome 1 (del 1p) is a Strong Predictor of Poor Outcome in Myeloma Patients Undergoing an Autotransplant

Abstract: Several chromosomal abnormalities detected by conventional cytogenetic analysis have an adverse impact on the outcome in myeloma patients. A wide spectrum of abnormalities involving chromosomes 1, 13, 14, and 17 has been described. We analyzed the outcome of 83 patients with clonal cytogenetic abnormalities, who underwent high-dose therapy and autologous stem cell transplantation for multiple myeloma at our institution. Clonal abnormalities were detected at diagnosis by conventional cytogenetic analysis in 83 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…confirms the aneugenic effect of topotecan containing regimens in vivo reported by Qazilbash et al [2007], where in bone marrow from cancer patients, an increase in the hyperdiploidy and deletion of chromosome 13, using Gbanding technique, was observed. Of the signal-positive MN, 45 (56.9%) had one signal, 24 (30.4%) contained two signals, and 10 (12.7%) had 3 signals.…”
Section: Resultssupporting
confidence: 84%
“…confirms the aneugenic effect of topotecan containing regimens in vivo reported by Qazilbash et al [2007], where in bone marrow from cancer patients, an increase in the hyperdiploidy and deletion of chromosome 13, using Gbanding technique, was observed. Of the signal-positive MN, 45 (56.9%) had one signal, 24 (30.4%) contained two signals, and 10 (12.7%) had 3 signals.…”
Section: Resultssupporting
confidence: 84%
“…In a work by Walker et al 12 , the incidence of deletion 1p rose to 30% (24% in the work of Avet-Loiseau et al 11 ). In 2007, Giralt 14 et al identified deletion 1p in 18% of patients and found an association with a significantly shorter PFS and OS. Boyd et al 13 have published a study of deletions at 1p12, 1p22 and 1p32 where del(1p32) was present in 11.3% of patients and impaired survival (34.5 months versus not reached, p<0.001) and 1p22 did not affect survival although it was the most frequently deleted region (22.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the structural aberrations in MM occur in chromosome 1. Deletions generally involve in 1p whereas amplifications correspond to 1q (Le Baccon et al, 2001;Qazilbash et al, 2007).…”
Section: Chromosomal Abnormalitiesmentioning
confidence: 99%